Purification and biochemical characterization of recombinant Persicaria minor β-sesquiphellandrene synthase - De-Sheng Ker; Sze Lei Pang; Noor Farhan Othman; Sekar Kumaran; Ee Fun Tan; Thiba Krishnan; Kok Gan Chan; Roohaida Othman; Maizom Hassan; Chyan Leong Ng (PeerJ, 2017)
Background Sesquiterpenes are 15-carbon terpenes synthesized by sesquiterpene synthases using farnesyl diphosphate (FPP) as a substrate. Recently, a sesquiterpene synthase gene that encodes a 65 kDa protein was isolated from the aromatic plant Persicaria minor. Here, we report the expression, purification and characterization of recombinant P. minor sesquiterpene synthase protein (PmSTS). Insights into the catalytic active site were further provided by structural analysis guided by multiple sequence alignment. Methods The enzyme was purified in two steps using affinity and size exclusion chromatography. Enzyme assays were performed using the malachite green assay and enzymatic product was identified using gas chromatography-mass spectrometry (GC-MS) analysis. Sequence analysis of PmSTS was performed using multiple sequence alignment (MSA) against plant sesquiterpene synthase sequences. The homology model of PmSTS was generated using I-TASSER server. Results Our findings suggest that the recombinant PmSTS is mainly expressed as inclusion bodies and soluble aggregate in the E. coli protein expression system. However, the addition of 15% (v/v) glycerol to the protein purification buffer and the removal of N-terminal 24 amino acids of PmSTS helped to produce homogenous recombinant protein. Enzyme assay showed that recombinant PmSTS is active and specific to the C15 substrate FPP. The optimal temperature and pH for the recombinant PmSTS are 30 °C and pH 8.0, respectively. The GC-MS analysis further showed that PmSTS produces β-sesquiphellandrene as a major product and β-farnesene as a minor product. MSA analysis revealed that PmSTS adopts a modified conserved metal binding motif (NSE/DTE motif). Structural analysis suggests that PmSTS may binds to its substrate similarly to other plant sesquiterpene synthases. Discussion The study has revealed that homogenous PmSTS protein can be obtained with the addition of glycerol in the protein buffer. The N-terminal truncation dramatically improved the homogeneity of PmSTS during protein purification, suggesting that the disordered N-terminal region may have caused the formation of soluble aggregate. We further show that the removal of the N-terminus disordered region of PmSTS does not affect the product specificity. The optimal temperature, optimal pH, Km and kcat values of PmSTS suggests that PmSTS shares similar enzyme characteristics with other plant sesquiterpene synthases. The discovery of an altered conserved metal binding motif in PmSTS through MSA analysis shows that the NSE/DTE motif commonly found in terpene synthases is able to accommodate certain level of plasticity to accept variant amino acids. Finally, the homology structure of PmSTS that allows good fitting of substrate analog into the catalytic active site suggests that PmSTS may adopt a sesquiterpene biosynthesis mechanism similar to other plant sesquiterpene synthases.